Juridical Analysis of Good and Correct Application of Indonesian Language in Legal Professionals - Nurhilmiyah Nurhilmiyah (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
Bahasa Indonesia is a language used in the field of law in Indonesia, and has its own characteristics. therefore legal language must meet the Indonesian language terms and rules. Legal language is actually part of Indonesian too. Indonesian language with a variety of laws is one of the various Indonesian languages that are used as communication tools by people who are involved in the field of law or studying law. The variety of legal languages, must pay attention to the structure or rules of the standard Indonesian language. Therefore, legal language should not prioritize language style but prioritize legal certainty. Legal professionals that include academics and important legal practitioners master language skills. Because the field of law cannot be separated from the application of language. Legal products are written in language. According to previous research, there are various deviations in the prevailing Indonesian rules. both in case files, agreement letters, notary deeds, and statutory regulations. This writing wants to find answers to the problem formulation, how is the regulation regarding Indonesian in positive law. And how should the application of Indonesian language be good and right for legal professionals